"we are people!": narratives of women trans about Human Rights (Tempo e Argumento, 2020)
This article aims to present the discussion about Human Rights in the present time, from the oral narratives of four trans women, living in cities of southern Minas Gerais: Luana, Lucielly, Wall and Ana Luíza. Their life stories are important testimonies that reveal not only their personal experiences, but a culture of violations of the rights of LGBT populations, especially of trans people, built throughout history. The narratives denounce the permanence of practices and discourses that, although they defend the universal idea of law and of people, are also used to disrespect the differences, denying the possibility of constructing the dignity to certain groups. Such works put the historian of the present time before an ethical commitment to register and publicize these stories in search of social transformation and the defense of life.Keywords: Human Rights. Transsexuality. Dignity. Present Time.